Border Residents and Cross border Crimes in Ghana: An Empirical Study of Aflao (International Journal of Scientific Research and Management (IJSRM), 2018)
Border residents have been noted for their involvement in goods smuggling and other illegal cross border exchanges as coping mechanisms for poverty and unemployment. This study assesses the veracity of this claim through a field survey of the eastern border town of Aflao. The result of the study shows that challenges of poverty and unemployment have forced border residents to exploit their location in the border space as coping strategy by engaging in officially proscribed activities. These activities involve crimes such as goods smuggling, smuggling facilitation, armed robbery and petty stealing, drug trafficking, human trafficking and arms trafficking. While border residents are likely to see some of these activities (armed robbery and petty stealing, drug trafficking, human trafficking and arms trafficking) as crimes, they would normally accept that goods smuggling and aiding smuggling are not crimes because they serve as livelihood options, which contribute to reducing unemployment and poverty in border areas. To be effective, border management has to be comprehensive and incorporate the livelihood needs of Borderlanders.